The Role of Motivational Interviewing in Improving Health State of Patients Undergoing Hemodialysis - Rassoul Abdulzahra Mankih, Ala`A Hassan Mirza Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hemodialysis patients frequently experience social, psychological, and physical issues. Motivational interviewing is one of the most crucial methods for patients’ health promotion .Patients undergoing hemodialysis need to more attention and care by educating about diseased condition and motivating them to adhere to treatment to reduce their suffering Aims of the study: To determine the role of motivational interviewing in improving the health status of patients undergoing hemodialysis. Methodology: A Single blind, randomized, clinical trial was conducted on patients on hemodialysis who were referred to Hemodialysis Unit of Al-Sadder Hospital, Missan, Iraq. for the period (first of February to 15th Maye, 2022). The participants were selected through purposive sampling method and were placed in two groups, each group contained (30) patients, one of these groups was intervened by motivational interviewing program and represented as an experimental group, while the other group acted as control group. The experimental group received five sessions of motivational interviewing. The General Health Questionnaire (GHQ) was completed by the participants before and after the intervention. Results: Results presented that there was a significant effect of the motivational interviewing on patients with hemodialysis of the experimental group at P = .000, while no significant difference (P = .083) appeared on control group who did not receive the motivational interviewing. motivational interviewing improved all aspects of general health status, based on general health questionnaire as a comparing between the pre and posttest time for the experimental group of all domains at P value less than .05. Conclusion: The program of motivational interviewing has a positive effect of on the treatment adherence in hemodialysis patients using both objective and subjective parameters as well as plays a significant role in the entire aspects covered by HPL-II including; physical activity, nutrition, spiritual growth, personal relationships, stress management, health responsibility